Relationship building in a cross-cultural setting: the importance of intercultural competence - Brunner, Jason M. (Kansas State University, 2010)
The current study uses structural equation modeling to simultaneously test the relationships between cultural knowledge, rapport building, and counterpart receptiveness in a cross-cultural setting using military-advisors. Five-hundred-eighty-three Army soldiers and Marines deployed to either Iraq or Afghanistan as advisors to host-national soldiers were asked to complete a questionnaire about their job-tasks. Results indicate that advisors who use cultural knowledge are more effective building relationships, and as a result have counterparts who are more receptive to their advice. Limitations and implications of the model are discussed, as well as potential directions for future research.
Keywords: Cross-culture; Cultural knowledge; Psychology, Industrial (0624)